Lactarius subgenus Russularia (Russulaceae) in South-East Asia: 3. new diversity in Thailand and Vietnam - Wisitrassameewong, Komsit; Nuytinck, Jorinde; Le, Huyen Thanh; de Crop, Eske; Hampe, Felix; Hyde, Kevin D; Verbeken, Annemieke (Phytotaxa, 2015)
Lactarius subgenus Russularia is a dominant group of milkcaps in Southeast Asia. This paper reveals the large diversity of the subgenus, with eight new species and one known species being described from montane evergreen and coniferous forests. All new species are supported by both morphological and molecular data, the latter using Maximum likelihood and Bayesian analysis based on the ITS region. Complete macro- and micro-morphological descriptions and illustrations are given. A key to the new taxa is provided. Lactarius chichuensis is reported for the first time from Thailand.